تمثلات الشخصية اليهودية وتجليات الخطاب اليهودي في رواية "في قلبي أنثى عبرية" لخولة حمدي - بوشلاق, حكيمة (جامعة الوادي - University of Eloued, 2021)
تعتبر الشخصية أهم ركن من أركان البناء السردي في كل عمل روائي ولا تخلو رواية من الروايات من ذكر للشخصيات على اختلاف أدوارها من الرئيسية على الثانوية إلى الهامشية، وتنوع موضوع الرواية فنجد الرواية الاجتماعية والسياسية والعلمية والتاريخية إلى الدينية وغيرها من المجالات . وفي الرواية الدينية برز الكثير من الروائيين وكتبوا فيها وذكروا الديانات الاسلامية والمسيحية واليهودية، هذه الديانة تجلَّت بشكل واضح في رواية " في قلبي أنثى عبرية" للروائية خولة حمدي؛ حيث تمظهرت فيها الشخصية اليهودية بتصرفاتها ومعاملاتها مع الآخر، كما تجلى فيها الخطاب اليهودي الذي كان يحثُّ على الابتعاد عن الدين الإسلامي وعدم اعتناقه، فكانت ثنائية الحب والدين متجلية في نص الرواية؛ ولأجل الحب والتسامح اعتنقت العديد من الشخصيات الدين الإسلامي وانتصر الإسلام في أخر الرواية. The character is considered as the most important element in the narrative structure, in every novel, with the variance of its roles including principal, secondary, and marginal ones. The novel topic differs from social, political, scientific, historical, and religious and other fields. In the religious novel, there’re prominent novelists , who mention Islam, Christianity, and Judaism. This latter has been so clear in Khawla Hamdi’s novel “A Hebrew girl in my heart”. The Jewish character deeds and the way of the other treatment is shown. The Jewish discourse is also shown; it invites getting away from Islam and not believing in. So, the dichotomy of love and religion is so clear in the novelistic text. For the sake of love and forgiveness, several characters start believing in Islam, which overcomes other religions at the end of the novel.
مقال
Keywords: في قلبي أنثى عبرية، تجليات الخطاب اليهودي، تمثلات الشخصية اليهودية، الشخصيات المسلمة في الرواية، الشخصيات المسيحية في الرواية; “A Hebrew girl in my heart”, the Jewish discourse aspects, the Jewish character representations, Islamic characters in the novel, the Christian characters in the novel